“Gamolan Pekhing”: Telaah Filsafat pada Kesenian Masyarakat Lampung - Riyan Hidayatullah (Institut Seni Indonesia Denpasar, 2022)
Purpose: This study attempts to describe the findings of field research. Data from observations and interviews with key informants were analyzed from the standpoint of the philosophy of science. Philosophy is made up of three major components: ontology (knowledge), epistemology (methodology), and axiology (values). Research Methods: Gamolan pekhing's musical elements are described as a form of ontological reality. Furthermore, in terms of epistemology, explaining the process of establishing the gamolan pekhing music tradition as established knowledge. Gamolan pekhing music is axiologically directed to an awareness of the value of usefulness. Results and Discussion: As a result, the ontology of gamolan pekhing music applies the concept of mimesis (imitation) to an already existing reality. The form of imitation is represented by musical instruments and the system of scales. Implication: The epistemological aspect reveals the limits, sources, structure, and validity of knowledge. The gamolan pekhing music tradition establishes an ecosystem in which its elements thrive. On the axiological relevance of gamolan pekhing, the ecosystem includes musicians, craftspeople, musical materials, musical works, inheritance models, learners, and notation systems. Music will continue to impact the community that supports it positively. Because of these values, gamolan pekhing music has survived today.